Provision of Humanitarian Aid by BKM Mu'allimin to Flash Flood Victims in Aceh Tamiang as a Form of Concern from the Congregation and Community - A. Zebar (Outline Publisher, 2026)
Flash floods are among the most destructive hydrometeorological disasters, causing significant social, economic, and humanitarian impacts on affected communities. Such conditions require the active involvement of various stakeholders, including religious institutions, in providing timely and effective humanitarian assistance. This community service program aimed to deliver humanitarian aid to communities affected by the flash flood disaster in Aceh Tamiang Regency while fostering social awareness and solidarity among mosque congregants through donation campaigns. The program employed a participatory approach consisting of committee formation, fundraising through donation boxes, bank transfers, and public announcements to the congregation, followed by the collection and packaging of relief supplies, aid distribution in collaboration with local volunteers, and documentation and evaluation of the activities. The results demonstrated that the program was successfully implemented with strong participation from mosque congregants and the wider community, who contributed both financial donations and essential relief items. The assistance was distributed effectively and reached the intended beneficiaries through close coordination with local volunteers and community leaders. In addition to meeting the victims' immediate basic needs, the program strengthened the social role of BKM Mu'allimin as a center for humanitarian services while promoting solidarity, mutual cooperation, and community engagement. This initiative is expected to serve as a replicable mosque-based community service model for disaster response and humanitarian assistance in other disaster-prone regions.